2006
DOI: 10.1177/0306624x05285093
|View full text |Cite
|
Sign up to set email alerts
|

Is Schizoid Personality a Forerunner of Homicidal or Suicidal Behavior?

Abstract: The authors believe that a relationship exists between schizoid personality disorder and violent acts. The following case study is presented to contemplate such a possible relationship. There is a paucity of research on this topic. The authors suggest that further research closely examine the relationship between violent behavior and those character traits associated with schizoid personality disorder. If such a relationship is found, these character traits could be integrated with other risk factors known to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…Schizoid PD is related as well with features of psychopathy and Antisocial personality according to Kosson et al [ 34 ]. Loza and Hanna argue that an association exists between Schizoid PD and violent acts [ 35 ]. This study found a significant relation only of “Cluster A” disorders with violent offenses.…”
Section: Discussionmentioning
confidence: 99%
“…Schizoid PD is related as well with features of psychopathy and Antisocial personality according to Kosson et al [ 34 ]. Loza and Hanna argue that an association exists between Schizoid PD and violent acts [ 35 ]. This study found a significant relation only of “Cluster A” disorders with violent offenses.…”
Section: Discussionmentioning
confidence: 99%
“…Asimismo, es posible que sujetos con trastorno esquizoide de la personalidad se vean implicados en comportamientos violentos autoagresivos (suicidios) o heteroagresivos (homicidios) (Loza y Hanna, 2006).…”
Section: Repercusiones Forenses Del Trastorno Esquizoide De La Personunclassified
“…Les résultats similaires obtenus dans ces divers milieux ont permis de confirmer que la relation entre ces troubles de personnalité et les comportements violents est présente dans ces diverses populations (Berman et al, 1998 ;Blonigen et Krueger, 2007 ;Fountoulakis et al, 2008 ;Loza, 2003 ;Loza et Hanna, 2006 ;Tardiff, 2001 ;Widiger et Trull, 1994). D'autres études ont permis de constater que des facteurs comme la consommation de substances psychoactives, les abus dans l'enfance, le fait d'avoir évolué dans un milieu criminel en bas âge peuvent solidifier le lien entre les comportements violents et les troubles de personnalité (Fountoulakis et al, 2008 ;Friedmann et al, 2008 ;Goethals et al, 2008).…”
Section: Troubles De Personnalité Et Violenceunclassified